2014
DOI: 10.1002/ejoc.201301760
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Flexibility of Strychnine

Abstract: H and 13 C NMR spectra were recorded on a Bruker DRX 500 instrument (BBO probe) at 500.13 and 125.76 MHz, respectively, in steps of 10 K between 210 and 280 K (15 mg of the base form in 600 L CDCl 3 ), between 180 and 280 K (10 mg of the hydrochloride in 600 L [d4]methanol), and 298 K. Temperature calibration was done with a methanol reference sample. 1 H NMR spectra were acquired using a spectral width of 12 kHz, an acquisition time of 5.5 s and 16 scans, zerofilled to 128 k datapoints (0.09 Hz per point) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In addition, previous work on a minor conformer of strychnine indicated that the mpw1pw91/cc-pvdz level of theory is superior to the "working horse" of geometry optimization, i.e. B3LYP/6-31G(d) [17].…”
Section: Ordmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous work on a minor conformer of strychnine indicated that the mpw1pw91/cc-pvdz level of theory is superior to the "working horse" of geometry optimization, i.e. B3LYP/6-31G(d) [17].…”
Section: Ordmentioning
confidence: 99%
“…The latter point is also related to the accuracy with which the rotational strengths are calculated. Based on own results [17,60], we can assume differences of a factor of two between calculation and experiment concerning the rotational and dipolar strengths.…”
Section: Ecdmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed study of limonene has shown that the mpw1pw91/ccpvdz level of theory delivers reliable results for the calculation of 13 C chemical shifts [29]. In addition, this level of theory was successful in the geometry optimization of a low-populated conformer of strychnine, base and HCl [30,31].…”
Section: Structural Analysis Of the Menthol-type Isomersmentioning
confidence: 99%
“…A wide variety of structural factors can influence the magnitude of 1 J CC . For example, prior work has demonstrated that the 1 J CC coupling is sensitive to dihedral angle, where changes as large as 9 Hz between different conformations have been reported. Stereochemical configuration also influences 1 J CC coupling, where, for example, the 1 J CC coupling in methyl α‐D‐mannopyranoside differs from the β‐D‐mannopyranoside by 4 Hz .…”
Section: Introductionmentioning
confidence: 99%